Rancang Bangun Aplikasi Marketplace Jual Beli Sampah Daur Ulang Berbasis Web - Ananda, Luthfi Kamal; Hastuti, Khafiizh (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Something that is no longer used or thrown away resulting from human activities and does not occur by itself is called waste. Waste is a big problem for humans because of the large population where each individual definitely contributes waste to everyday life. The national waste pile in Indonesia at the end of 2022 will reach more than 21 million tons. Of the total waste production, 65.71% of waste can be managed, while the rest cannot be managed properly. To assist in waste management in Indonesia, researchers designed and developed the Reforma Trash application as a web-based marketplace for allocating waste and selling it to parties in need for recycling, crafts, etc. The application can be accessed by all Indonesian people and can calculate prices for shipping expedition services. This application was designed using Pressman's Waterfall SDLC method using Unified Modeling Language (UML) as a way to analyze the system and communicate the system design in paper form.